Determination of optimum quantity of bitumen in asphalt concrete mixtures - Vislavičius, Kęstutis (Journal of Civil Engineering and Management, 2002)
The problem of calculating the quantity of a required bitumen is formulated as follows: from certain mineral materials the grading curves and narrow fraction bitumen receptivities which are known to determine the composition of an asphalt concrete mixture that satisfies grading limitations of mineral materials and contains minimum quantity of a required bitumen. Mathematical analogues of the problem are presented. A personal computer programme for calculating the minimum quantity of a required bitumen is prepared, and some example problems are solved. An analysis of the results is presented.First Published Online: 30 Jul 2012